The TEACHING VOCABULARY THROUGH OPENING PLACE TECHNIQUE TO CLASS VIII OF SMP NEGERI 2 SEI LIPUT - TM Ridha Al auwal (Journal of Education, Linguistics, Literature and Language Teaching, 2018)
The research deals with teaching vocabulary through Opening Place Technique The purposes of this study is to find out causes which make students feel bored when learning in the classroom, causes which make students feel shy to speak and whether teaching vocabulary through opening place effective to make students interest and more active. The methodology in order to obtain the data for this research the writer used library and field research. In library research, the writer read some books, which are relevant to the topic from library and other sources and in the field research. Using this technique is one of the ways to solve students’ difficulties in learning vocabulary. It is increasing students’ interest and motivation in learning English. The teacher is also easier in teaching English especially vocabulary. The result of the research proved that the students’ achievement in mastering vocabulary can be influenced by the use of opening place technique